An asymmetric encryption method for 3D mesh model using elgamal with elliptic curve cryptography - Pongpisit Wuttidittachotti; Pornsak Preelakha (Institute of Advanced Engineering and Science, 2022)
The 3D mesh (Polygon mesh) model has been widely used in multiple computer technology fields such as computer graphic design and modern 3D animation. 3D mesh repositories were created to support the contribution of many 3D artist-designers and have become an important data source. This research is aimed at introducing asymmetric encryption for a 3D mesh model to improve encryption using elgamal elliptic curve cryptography with Fischer-Yates shuffling. The researchers evaluated the performance of the proposed model using Entropy, mean squared error (MSE), and peak signal noise ratio (PSNR) as evaluation matrices. The results of a decrypted model using our approach with a double-precision floating point showed zero means squared error and infinite value of PSNR.